2020
DOI: 10.1002/iub.2232
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of 6‐phosphofructo‐2‐kinase (PFKFB3) by hyperactivated mammalian target of rapamycin complex 1 is critical for tumor growth in tuberous sclerosis complex

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant disease characterized by the benign tumor formation in multiple organs. The main etiology of TSC is the loss‐of‐function mutation of TSC1 or TSC2 gene, which leads to aberrant activation of mammalian target of rapamycin complex 1 (mTORC1). In this research, we found a significant increase of 6‐phosphofructo‐2‐kinase/fructose‐2,6‐biphosphatase 3 (PFKFB3) expression in Tsc1−/− and Tsc2−/− mouse embryonic fibroblasts (MEFs) compared with the control cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“… 21 , 22 , 23 Using these cell models, we have previously reported that hyperactivated mTORC1 fosters tumor growth by manipulating the expression of multiple glycolytic enzymes, such as PKM2, LDHB, and PFKFB3. 13 , 17 , 24 , 25 RTKs have been shown to be aberrantly expressed in many tumors, including TSC. 26 However, in addition to PDGFRα and PDGFRβ, information on other RTKs that contribute to the development of TSC tumors is limited.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 23 Using these cell models, we have previously reported that hyperactivated mTORC1 fosters tumor growth by manipulating the expression of multiple glycolytic enzymes, such as PKM2, LDHB, and PFKFB3. 13 , 17 , 24 , 25 RTKs have been shown to be aberrantly expressed in many tumors, including TSC. 26 However, in addition to PDGFRα and PDGFRβ, information on other RTKs that contribute to the development of TSC tumors is limited.…”
Section: Discussionmentioning
confidence: 99%
“… 224 Therefore, there have been several drugs targeted at tumor aerobic glycolysis for cancer treatment, including 2‐Deoxyglucose 225 (the inhibitor of GLUT1 and HK), Dichloroacetate 226 (inducing a shift from glycolysis to OXPHOS), and the inhibitor of phosphofructokinase 1. 227 However, these drugs also significantly inhibit T cell function and promote immunosuppression. 228 Therefore, targeting tumors is important for the application of glycolysis inhibitors in tumor therapy.…”
Section: Metabolism and Cancer Immunotherapymentioning
confidence: 99%
“…PFKFB3 induces mTORC1 activity through expression of pS6K and increases mTORC1 lysosomal translocation independent of AMPK regulation [ 135 ]. Loss of function mutation of tuberous sclerosis complex 1 ( TSC1 ) or 2 ( TSC2 ) leads to accumulation of Rheb GTPase, which subsequently activates mTORC1 [ 144 ]. TSC LOH, as well as the resulting mTORC1 activation, has been extensively documented in astrocytoma, ependymoma, ganglioglioma, oligodendroglioma, and glioblastoma [ 145 ].…”
Section: Pfkfb3 In Central Nervous System Tumorsmentioning
confidence: 99%
“…TSC LOH, as well as the resulting mTORC1 activation, has been extensively documented in astrocytoma, ependymoma, ganglioglioma, oligodendroglioma, and glioblastoma [ 145 ]. Activated mTORC1 promotes the expression of HIF-1α, which subsequently increases PFKFB3 transcription and protein expression [ 144 ]. As PFKFB3 can be reciprocally induced by activated mTORC1, PFKFB3 appears to be involved in a vicious cycle of continuous overexpression and oncogenicity in various CNS tumors.…”
Section: Pfkfb3 In Central Nervous System Tumorsmentioning
confidence: 99%
See 1 more Smart Citation